2021
DOI: 10.3390/nano11102649
|View full text |Cite
|
Sign up to set email alerts
|

Metal Cluster Size-Dependent Activation Energies of Growth of Single-Chirality Single-Walled Carbon Nanotubes inside Metallocene-Filled Single-Walled Carbon Nanotubes

Abstract: By combining in situ annealing and Raman spectroscopy measurements, the growth dynamics of nine individual-chirality inner tubes (8,8), (12,3), (13,1), (9,6), (10,4), (11,2), (11,1), (9,3) and (9,2) with diameters from ~0.8 to 1.1 nm are monitored using a time resolution of several minutes. The growth mechanism of inner tubes implies two successive stages of the growth on the carburized and purely metallic catalytic particles, respectively, which are formed as a result of the thermally induced decomposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 130 publications
0
27
0
Order By: Relevance
“…The annealing of metallocene-filled SWCNTs leads to the decomposition of molecules with the formation of metal carbides and pure metals [7,21,29,30]. The encapsulated metal carbides and metals serve as catalysts for the inner tube growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The annealing of metallocene-filled SWCNTs leads to the decomposition of molecules with the formation of metal carbides and pure metals [7,21,29,30]. The encapsulated metal carbides and metals serve as catalysts for the inner tube growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the growth mechanism implies the stages of (i) decomposition of metallocene and (ii) growth of inner nanotubes on the metal carbide and metal particles. In [21,29,30], it was revealed that the growth mechanism of inner tubes includes two successive stages of the growth on carburized and purely metallic catalytic particles. Each stage is characterized with different growth rates and activation energies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endohedral metallofullerene DySc 2 N@C 80 were filled inside well-purified SWC-NTs [188,189] with a narrow diameter distribution of 1.4 ± 0.1 nm [184]. This encapsulation achieves a controllable and uniform enhancement of SMM properties.…”
Section: Spintronics 251 Overview Of Reportsmentioning
confidence: 99%
“…There is a special interest in using SWCNTs as enclosures for the encapsulation of payloads [6][7][8][9]. The nanotubes offer protection to the hosted material from the external environment, thus allowing, for instance, the encapsulation of air sensitive materials [10], gases [11], and even radionuclides [12,13].…”
Section: Introductionmentioning
confidence: 99%